Role of tungsten oxide (WO3) on thermal and optical properties of smart polymer composites - Aydin, Handan; Ozen Oner, Ecem; Aydin, Cihat (De Gruyter Poland Sp Z O O, 2025)
Tungsten oxide, a versatile transition metal with numerous polymorphs and sub-stoichiometric compositions, containing inherent tunnels and oxygen vacancies, has become a current field of study due to its rich crystal structure, high electrochemical stability, easy accessibility, and environmental friendliness. Thus, the versatile structure of WO3-based materials makes them promising candidates for advanced applications. Our study aims to provide valuable insights into the performance of these materials used in various fields. The structural, optical, and thermal characteristics of PVC-PCL composites doped with tungsten oxide (WO3) were examined in this work. According to DSC research, the thermal characteristics of the polymer matrix were significantly impacted by the addition of WO3. The thermal stability was found to have increased based on the TGA measurement findings. XRD analyses revealed that as the doping rate increased, improved crystallinity was seen. According to SEM tests, the grain clusters are uniformly mixed and the tungsten oxide is evenly spread across the surface. The dopant reacted either chemically or physically with the polymer matrix, according to the ATR-FTIR spectra of PVC-PCL matrix nanocomposite films. An improvement in conductivity with an increase in dopant concentration was noted in the optical experiments. Thus, it can be stated that PVC-PCL composites doped with WO(3 )can be used in optoelectronic, various industrial, and biomedical application areas due to their structural, optical, and thermal properties.
Keywords: tungsten oxide (WO3); polyvinyl chloride (PVC); polycaprolactone; composite; optical property